Compliance with WHO Surgical Safety Checklist in Otorhinolaryngology in a Tertiary Care Center: A Retrospective Study - Dongol, Kripa; Gautam, Shristi (Journal of Institute of Medicine Nepal, 2025)
Introduction Surgical safety checklist is crucial for patient safety and enhanced communication between operating team members. It decreases surgical morbidity and mortality. This study aimed to evaluate the utilization rate of Surgical Safety Checklist introduced by WHO and completion of its 19-items during Otorhinolaryngology surgery. MethodsThis was a cross-sectional, observational study conducted in Otorhinolaryngology Department of tertiary care center, Nepal from 14th April, 2024 to 15th October, 2024.  Surgical Safety Checklist attached in 111 charts of patients who had undergone surgeries of ear, nose, neck and throat under General Anesthesia were evaluated. Percentage of utilization and completeness of the checklist were calculated.ResultsThe utilization of the WHO Surgical Safety Checklist in Otorhinolaryngology was found to be 67.56% (75 out of 111 charts). The entirely filled checklist was observed in only 8 out of 75 (10.67%) charts. Seventy-one charts were of elective surgeries while only four charts were of emergency surgeries. Time-out section was completed in nearly hundred percent charts.  Sign-in was complete in 64 out of 75 (85.33%) charts. The least completed section was the sign-out section, which was filled in only 8 out of 75 (10.67%) charts.ConclusionUtilization of Surgical Safety Checklist in Otorhinolaryngology surgery was observed in two-thirds of the cases. However, its completeness was poor. Time-out was the most fulfilled section while sign-out was the least filled section in the checklist.